PERBANDINGAN MODEL PEMBELAJARAN DISCOVERI LEARNING DAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR KONSEP SISTEM PENCERNAAN MAKANAN PADA SISWA KELAS VIII SMP KRISTEN YPKPM AMBON - Dominggas Radjangolo; H Tuaputty; Ine Arini (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: The use of the right learning model is an alternative to overcome the problem of students' low absorption of lessons, in order to improve the quality of teaching. In its implementation, an appropriate learning model is needed that is able to arouse students' motivation to learn. The use of the right learning model is to use Discovery Learning models and Problem Posing learning models. Method: This study aims to determine the differences in student learning outcomes taught using Discovery Learning models and Problem Posing learning models on the concept of the digestive system in the food of class VIII students of YPKPM Christian Middle School Ambon. Results: Based on the results of the study the use of the Discovery learning model the average value of cognitive aspects = 87.82, the affective aspect = 80.88, the psychomotor aspects = 90.4, the final value = 94.64, the final test value = 94. While the model Problem Posing learning the average value on cognitive aspects = 95.49, affective aspects = 93.76, psychomotor aspects = 93.32, final value = 93.90 and final test value = 96.17. With t count 2.04 and t table 2.01. Conclusion: Student learning outcomes in the problem posing learning model class are higher than students in the class of discovery learning models.